Storm from the shadows [compact disc, unabridged] - Weber, David, 1952- (Weber, David, 1952- Honor Harrington., 2009)
When the Havenites take Rear Admiral Michelle Henke and her crew prisoner, they work out a prisoner exchange with Michelle's people. Little do the Havenites or Michelle's Manticore people know that the interstellar crime syndicate Manpower has ruthless and evil plans of their own.